The Storyboard Development of Virtual Reality Simulation (VRS) of Nursing Care in Respiratory System Disorders Course - Ryan Hara Permana; Mira Suryani; Dian Adiningsih; Erick Paulus (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2018)
Introduction :Practicingclinical nursing skills requires high fidelity learning methods but are often constrained by financial factors. Virtual Reality Simulation (VRS) is a practical learning method that is able to project visually the experience of practicing nursing care in a virtually real situation. VRS is financially affordable and portable, allowing students to learn whenever and wherever. This study focused on developing the storyboard of a VRS as a method of practicing nursing care skills in the case of acute respiratory system infection at Faculty of Nursing, Universitas Padjadjaran. Methods: This study utilized qualitative descriptive design.An expert group consists of a paediatric nurse, a senior paediatric nursing lecturer, an e-learning expert and two VR experts was working serially to develop the case and storyboard. The case development stage was conducted using a Focus Group Discussion (FGD) and the storyboard development stage used two workshop sessions. The NLN/Jeffries Simulation was used as a framework to develop the storyboard. Results: The learning objectives, scenes, actions, challenges and redirect elements were identified. The learning objectives is the most essential foundation in building a storyboard. Conclusion: The storyboard template allows subject matter experts to develop VRS that capable to train nursing care skills in a safe and immersive environment.